Sustainable utilisation of the River Ipel basin - Izakovičová, Zita; Oszlányi, Július (TÁJÖKOLÓGIAI LAPOK, 2010)
The study evaluates the territory River Ipel Basin in terms of sustainable development. The main objective is to define the existing landscape-ecological and environmental problems, to design measures for elimination of those problems and/or to prevent new problems. The ultimate goal of the effort is to achieve such management practices that are in harmony with the potential of the area in the highest possible extent. The basic principles applied in landscape-ecological optimising of landscape organisation include protection of nature, biodiversity and landscape stability, protection of natural resources including water, soil, air/atmosphere, forests, etc., protection of cultural-historical resources, including protection of cultural monuments, protection of historical landscape structures, etc., and environmental protection.